Diurnal activity pattern and behaviour of captive Prevost's squirrels (Callosciurus prevostii) - Zulaidi, Nurazreen; Bahaman, Abdul Rani; Babjee, Shaik Mohamed Amin; Sugnaseelan, Sumita (2010)
Wild populations of Prevost’s squirrel (Callosciurus prevostii) are currently threatened due loss of feeding and nesting sites as a consequence of habitat destruction and hunting activities. It is therefore important that efforts to conserve this species are initiated, to prevent the extinction of C. prevostii in the near future. In view of that, this study was undertaken to establish the diurnal activity pattern and behaviour of captive C. prevostii (n = 10), to warrant a better understanding of their biology which may assist in conservation efforts of this species. Data obtained through direct visual surveillance of the subjects whilst they were in their captive enclosure was feasible at a distance of 1.5 m. Behavioural measure were performed via scan sampling of the subjects every 10 minutes between 0700 and 1900 hours, over a period of 28 days. Captive C. prevostii spent a significant period in the daytime either resting or climbing. These behaviours were consistently high during both the conditioning and post-conditioning period which were 7 and 21 days, respectively. Locomotor stereotypy, namely pacing and circling, was also evident during the two observation periods and could be attributed to the natural active predisposition of C. prevostii, which is arboreal in the wild.